Early-life stress induces persistent astrocyte dysfunction associated with fear generalisation - Mathias Guayasamin; Lewis R Depaauw-Holt; Ifeoluwa I Adedipe; Ossama Ghenissa; Juliette Vaugeois; Manon Duquenne; Benjamin Rogers; Jade Latraverse-Arquilla; Sarah Peyrard; Anthony Bosson; Ciaran Murphy-Royal (eLife)
Early-life stress can have lifelong consequences, enhancing stress susceptibility and resulting in behavioural and cognitive deficits. While the effects of early-life stress on neuronal function have been well-described, we still know very little about the contribution of non-neuronal brain cells. Investigating the complex interactions between distinct brain cell types is critical to fully understand how cellular changes manifest as behavioural deficits following early-life stress. Here, using male and female mice we report that early-life stress induces anxiety-like behaviour and fear generalisation in an amygdala-dependent learning and memory task. These behavioural changes were associated with impaired synaptic plasticity, increased neural excitability, and astrocyte hypofunction. Genetic perturbation of amygdala astrocyte function by either reducing astrocyte calcium activity or reducing astrocyte network function was sufficient to replicate cellular, synaptic, and fear memory generalisation associated with early-life stress. Our data reveal a role of astrocytes in tuning emotionally salient memory and provide mechanistic links between early-life stress, astrocyte hypofunction, and behavioural deficits.